2012
DOI: 10.1100/2012/591816
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Evaluation of the Project P.A.T.H.S.: An Integration of Findings Based on Program Implementers

Abstract: An integration of the qualitative evaluation findings collected from program implementers conducting the Project P.A.T.H.S. (Positive Adolescent Training through Holistic Social Programmes) in different years (n = 177 participants in 36 focus groups) was carried out. General qualitative data analyses utilizing intra and interrater reliability techniques were performed. Results showed that the descriptors used to describe the program and the metaphors named by the informants that could stand for the program wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…This observation provides support for the effectiveness of the program from a triangulation perspective. Although other findings examining the S2 program of the Full Implementation Phase have yet to be published, similar positive findings were found in process evaluation, interim evaluation, and qualitative evaluation of instructors conducted in the Experimental Implementation Phase [21,22,23,24]. Taken together, these research findings consistently demonstrated the successful implementation of the S2 program.…”
Section: Discussionsupporting
confidence: 72%
“…This observation provides support for the effectiveness of the program from a triangulation perspective. Although other findings examining the S2 program of the Full Implementation Phase have yet to be published, similar positive findings were found in process evaluation, interim evaluation, and qualitative evaluation of instructors conducted in the Experimental Implementation Phase [21,22,23,24]. Taken together, these research findings consistently demonstrated the successful implementation of the S2 program.…”
Section: Discussionsupporting
confidence: 72%
“…Shek 2016 found that students generally held positive views of program instructors, content, and overall effectiveness. In addition, program implementers (teachers and school social workers) also perceived the PYD programs to be beneficial to adolescent positive development (Shek 2012;Shek and Ma 2012b). Taken as a whole, the findings in the present study suggest that community-based project in Hong Kong is effective in promoting students' PYD qualities, including a range of psychosocial competences which can promote adolescents' mental health.…”
Section: Discussionmentioning
confidence: 50%
“…Shek (2016) found that students generally held positive views of program instructors, content, and overall effectiveness. In addition, program implementers (teachers and school social workers) also perceived the PYD programs to be beneficial to adolescent positive development (Shek 2012;Shek and Ma 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…As positive youth development programs such as the Project P.A.T.H.S. can promote adolescent development and reduce adolescent risk behavior [4549], it would be exciting to see whether such programs can reduce adolescent pornographic behavior. Furthermore, as pointed out by Hald [13], “future research (should) focus on these situational, interpersonal, interpersonal, and behavioral characteristics of pornography consumption in addition to actual prevalence rates of consumption in different cultures” (p. 584).…”
Section: Discussionmentioning
confidence: 99%